Assessing the fungal contamination and potential impact of ochratoxigenic Aspergillus species on cocoa beans from cocoa-growing regions of Ghana - Banahene, Joel Cox Menka; Ofosu, Isaac Williams; Lutterodt, Herman Erick; Ellis, William Otoo (Science progress (1916), 2025)
Objective: This study investigated the fungal contamination profile of cocoa beans from cocoa-growing regions in Ghana, with particular emphasis on the potential impact of ochratoxigenic Aspergillus species. Methods: A total of 104 fermented and dried cocoa beans were randomly collected from farmers for analysis. Fungal isolation was conducted using potato dextrose agar and malt extract agar media. Species-level identification was performed through macroscopic and microscopic techniques. Ochratoxin A (OTA) quantification and confirmation were carried out using high-performance liquid chromatography with fluorescence detection and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: The investigation revealed 163 fungal isolates representing 14 distinct species across 10 genera. Aspergillus species, including Aspergillus flavus, Aspergillus niger, Aspergillus parasiticus, and Aspergillus fumigatus, were predominant. No statistically significant differences in fungal species occurrence were observed among the different cocoa-growing regions. However, certain species exhibited preferential growth on specific media, emphasizing the importance of medium selection in mycological studies. Of the 14 fungal species tested, only Aspergillus niger demonstrated the ability to produce OTA in vitro, as confirmed by LC-MS/MS analysis. Conclusion: This discovery holds substantial implications for both the cocoa industry and public health, considering that OTA is a potent mycotoxin subject to strict regulatory limits in food commodities. It is crucial to implement enhanced monitoring and control measures to mitigate fungal contamination in cocoa beans, particularly targeting OTA-producing species. The study also highlights the need for improved post-harvest handling practices, optimized storage conditions, and potential biocontrol approaches.